2008
DOI: 10.1152/japplphysiol.90613.2008
|View full text |Cite
|
Sign up to set email alerts
|

Human cerebral arteriovenous vasoactive exchange during alterations in arterial blood gases

Abstract: Evidence from animal studies indicates that various vasoactive factors, including release of norepinephrine, endothelin, adrenomedullin, C-natriuretic peptide (CNP), and nitric oxide (NO), may play a role in arterial blood gas-induced alterations in CBF. For the first time, we directly quantified exchange of these vasoactive factors across the human brain. Using the Fick principle and transcranial Doppler ultrasonography, we measured CBF in 12 healthy humans at rest and during hypercapnia (4 and 8% CO 2), hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 65 publications
1
51
2
Order By: Relevance
“…Indomethacin did not alter either the cerebrovascular or the ventilatory responsiveness to hypoxia responsiveness to CO 2 . Numerous studies have provided evidence, which support the validity of MCAv as an index of regional CBF (Bishop et al 1986;Nuttall et al 1996;Peebles et al 2008;Serrador et al 2000;ter Minassian et al 1998;Valdueza et al 1997). Moreover, studies have shown that the MCA diameter is relatively unchanged in the range of 23-60 mmHg for P a O 2 (Giller et al 1993;Serrador et al 2000;Valdueza et al 1997).…”
Section: Assessment Of Cbfmentioning
confidence: 85%
“…Indomethacin did not alter either the cerebrovascular or the ventilatory responsiveness to hypoxia responsiveness to CO 2 . Numerous studies have provided evidence, which support the validity of MCAv as an index of regional CBF (Bishop et al 1986;Nuttall et al 1996;Peebles et al 2008;Serrador et al 2000;ter Minassian et al 1998;Valdueza et al 1997). Moreover, studies have shown that the MCA diameter is relatively unchanged in the range of 23-60 mmHg for P a O 2 (Giller et al 1993;Serrador et al 2000;Valdueza et al 1997).…”
Section: Assessment Of Cbfmentioning
confidence: 85%
“…In young healthy adults, the response to changing CO 2 concentration is estimated at~1 to 2 mL/100 g per minute per unit CO 2 rise in the 30 to 40 mm Hg range. 31 The response is greater under hypercapnic conditions. Our results (Figures 3 and 5) indicate a lower response, with the overall slope equal to 0.43 mL/100 g per minute.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the sound attenuation inherent to ultrasound propagation through the skull, TCD provides only a measure of blood velocity, but not diameter, within the insonated vessel. A constant diameter is therefore assumed (Peebles et al, 2008) such that changes in flow can be inferred. If diameter does change with exercise than the reported velocity measures may not be indicative of flow.…”
Section: Limitations and Implicationsmentioning
confidence: 99%